Kinerja Pejabat Pengelola Informasi dan Dokumentasi (PPID) Kabupaten Bungo dalam Pemenuhan Ketersediaan Informasi Publik - Sari, Mela; Mulyadi, Rizky (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2020)
Access to services in accordance with the Public Information Disclosure Act directs all public bodies that utilize state/local budgets, must have Pejabat Pengelola Informasi dan Dokumentasi (PPID) whose duties and obligations provide information services to the public in order for the distribution of information so that aspects that prioritize services can occur properly. This study examines how the PPID performance of Bungo Regency Government in the fulfillment of public information availability. This research uses a qualitative method with descriptive analysis. Data analysis techniques using the model of Miles and Huberman. Furthermore, this study uses a data validity experiment using the Triangulation Method, namely by comparing information or data in different ways to obtain the correctness of information. The results showed that the performance of PPID Bungo Regency in the fulfillment of the availability of public information has not been maximally shown resulting in the service of unsatisfactory information received by the community. The cause is due to the lack of public information. The public does not always get the public information that is intended. Nevertheless, the development of public data/information has not been carried out. As the main provider of public information, the Regional Device Organization (OPD) as the Auxiliary PPID in Bungo Regency has not performed the function of depositing information to the main PPID by applicable rules.